Iron uptake by human upper small intestine microvillous membrane vesicles. Indication for a facilitated transport mechanism mediated by a membrane iron-binding protein. - Teichmann, R; Stremmel, W (The Journal of Clinical Investigation, 1990)
To investigate the hypothesis that iron absorption in man involves a carrier-mediated cellular uptake mechanism, influx velocity (Vo) of 59Fe3+ by isolated human microvillous membrane (MVM) vesicles of the upper small intestine was examined. Vo revealed saturation kinetics (Km = 315 nM; Vmax = 361 pmol Fe3+ x min-1 x mg protein-1) was temperature dependent and inhibited by pronase pretreatment of MVM. In the presence of an inwardly directed Na(+)-gradient a typical overshoot phenomenon with maximal uptake at 30-40 s was observed. The suggestion of an active, carrier-mediated uptake mechanism for iron was pursued by isolation of a 160-kD iron-binding protein from solubilized human MVM proteins. This glycoprotein was assembled as a trimer composed of 54-kD monomers. A monospecific antibody against the 54-kD subunit inhibited vesicular influx of Fe3+ into MVM by greater than 50%. Immunofluorescence and immunoblot analysis confirmed the localization of the protein in brush border plasma membranes. It was detectable in human intestinal mucosa and liver, but not in esophagus. These data indicate that the translocation of Fe3+ across human MVM represents a facilitated transport mechanism which is, at least in part, mediated by a membrane iron-binding protein. Images